Pemberdayaan Masyarakat Dalam Pembangunan Pertanian Berkelanjutan (Studi Pada Desa Asmorobangun Kecamatan Puncu Kabupaten Kediri) - Lifa Indri Astuti (Jurnal Administrasi Publik, 2015)
Abstract: Community Empowerment in Sustainable Agricultural Development (Study at Desa Asmorobangun, Kecamatan Puncu, Kabupaten Kediri). One of the duties of the nation is to provide the prosperity for the citizen through a development. The development is conducted by the government in order to reach the economic growth by utilizing all agriculture potentials and by organizing community development. In this study has yhe purpose is to know, describe and analyze the empowerment of the community in the village of Asmorobangun in sustainable agricultural development. Type of research is descriptive with qualitative approach data analysis uses Creswell’s model. Asmorobangun Village has a resource potential that is needed can apply sustainable agriculture development for community welfare. Through empowerment which involves several stages such as enlightenment, capacity building, and enforcement, hereby, the awareness, capacity, skill and strength of the community can be improved to exploit all potentials. The support given to the community in sustainable agriculture development is already not maximum. Despite this support, there are factors constraining community empowerment in sustainable agriculture development. These constraints may come from community, very few numbers of agriculture counselor, natural resource inadequacy, and also weather factor at Asmorobangun Village such that the empowerment process cannot be made maximum. Keywords: community empowerment, development, sustainable agriculture Abstrak: Pemberdayaan Masyarakat Dalam Pembangunan Pertanian Berkelanjutan (Studi Pada Desa Asmorobangun, Kecamatan Puncu, Kabupaten Kediri). Salah satu tugas negara adalah mensejahterakan warga negaranya yang dapat diwujudkan melalui pembangunan. Pembangunan yang dilakukan pemerintah untuk mencapai pertumbuhan ekonomi dengan memanfaatkan potensi pertanian yang dimiliki melalui pemberdayaan masyarakat. Pada penelitian ini memiliki tujuan yaitu mengetahui, mendiskripsikan, dan menganalisis pemberdayaan masyarakat di Desa Asmorobangun dalam pembangunan pertanian berkelanjutan. Jenis penelitian ini adalah deskriptif dengan pendekatan kualitatif menggunakan analisis model Creswell. Desa Asmorobangun memiliki potensi sumber daya dapat menerapkan pembangunan pertanian berkelanjutan untuk kesejahteraan masyarakat. Melalui proses pemberdayaan yang dilakukan dengan tahap penyadaran, pengkapasitasan dan pendayaan masyarakat dapat meningkatkan kesadaran, kemampuan, keahlian dan kekuatan untuk memanfaatkan potensi yang dimiliki. Dukungan yang diberikan kepada masyarakat untuk pembangunan pertanian berkelanjutan belum maksimal. Selain dukungan masih terdapat hambatan yang dihadapi dalam pemberdayaan masyarakat dalam pembangunan pertanian berkelanjutan. Hambatan yang dihadapi berasal dari masyarakat, kuantitas penyuluh pertanian, keterbatasan sumber daya alam yang belum mencukupi serta faktor cuaca di Desa Asmorobangun sehingga proses pemberdayaan kurang maksimal. Kata kunci: pemberdayaan masyarakat, pembangunan, pertanian berkelanjutan